Living arrangement of older population in rural Malaysia - Wan Ahmad, Wan Ibrahim; Ismail, Zainab; Redzuan, Ma'rof (American-Eurasian Network for Scientific Information, 2012)
One of the most significant demographic changes of the twentieth century is the aging of the world’s population. At the same time industrialization that taking place in developing countries has created a new pattern of family structure, that is nuclear conjugal family that resulting family care for the older persons become problematic. The purpose of this paper is to analyze the living arrangement of the older persons in rural Kelantan, Malaysia. The design in this study was a cambination of the sociological method of face-to-face interviews, and the anthropological method of participant-observation. Results show that nearly half of the respondents still living in the extended family, but the majority of the them feel that they want to choose to be living with their spouse only.